Situation of Oral Health Promotion Service for Pregnant Woman and Preschool Children in Chumphon Province During 2017-2021 - ภูติประวรรณ สุเทพ (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2022)
The objective was to 1) study the situation of oral health promotion programs provided and 2) suggest proposals for the development of oral health promotion services for pregnant women and early childhood in Chumphon Province.he secondary data was used from two sources: the website of the Health Data Center, the Ministry of Public Health and oral health surveillance and risk factor reports. The samples were pregnant women and preschool children who received oral health promotion services, children aged 18 months in Well Child Clinic and children aged 3 years in child care centres. The descriptive statistics were used and interviewed dental personnel, then content analysis was performed. The result showed that the hospitals and primary care units provided oral health promotion programs. The percentage of caries prevalence among 18-month children decreased from 11.7 in 2017 to 9.1 in 2019. More than half of the children still drank bottled milk, consumed snacks 1-2 times per day and their parents brushed their child’s teeth once a day. Among 3-year-old children, the percentage of caries prevalence increased from 49.3 in 2017 to 54.7 in 2019. Approximately 96% of child care centres implemented an after-lunch tooth brushing program and provided snacks for about 25%. All child care centres provided fruit 3-5 days per week, plain milk and dental examination by child caregivers (39.3%) and health personnel (94.6%) to children in 2019. The suggestions for service delivery improvement were service units should plan for procurement of hand-on tooth brushing sets and improve child management skills of dental personnel.